Pharmaceutical advertising and the consumption of over the counter (OTC) medicines in users of the SUPERFAR drugstore in Barrios Altos-Cercado de Lima, 2022. - Esteves Pairazaman, Ambrocio Teodoro (2022)
To determine the relationship between pharmaceutical advertising and the consumption of over-the-counter (OTC) medicines in users of the SUPERFAR drugstore in Barrios Altos-Cercado de Lima, 2022.